PANCA SATYA TERSIRAT DALAM EPOS MAHABHARATA SEBAGAI PENDIDIKAN KARAKTER GENERASI HINDU - Putu Ari Natih (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The epic Mahabharata is a story of heroism originating from the Hindu religious scriptures part of the Itihasa book which consists of 18 parwa. Of the eighteen parwa contain many ethical and moral teachings to be used as guidelines in character education today, because there is a lot of moral degradation which greatly affevts the character of a child. In this paper we will explore one of the teachings of panca satya through character plays which are told in several parwa sections. The teachings of the panca satya are teachings about loyality, honesty and based on truth, which consists of satya wecana which is loyal to word, satya mitra is loyal to friends, satya laksana isloyal to the actions that are done, satya hredaya is true to conscience, and satya semaya is true to promise. Of the five parts of the panca satya that are implied in the Mahabharata epic, it is very thick with character education that emphasizes honest, responsible, independent, religious, friendly, creative, curiosity, love of the country, hard work, respect for prestige, and social care. The purpose of this paper is to adopt the characters of several plays as contained in the educational curriculum which emphasizes 18 characters. This type of research is qualitative by using the story analysis method.